1977
DOI: 10.1016/s0022-5347(17)58393-7
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Circulating Antisperm Antibodies to Functional Success in Vasovasostomy

Abstract: The serum of 45 men with sperm in the ejaculate post-vasovasostomy was tested for antisperm antibodies. Agglutinating antibodies were found in 48 per cent of the men whose partners became pregnant and in 94 per cent of those whose partners did not become pregnant (p less than 0.01). No such correlation was found for sperm immobilizing antibodies. Spontaneous in vivo autoagglutination was not demonstrated in any of the patients. Although functional failure seems likely to be associated with an immunologic event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

1979
1979
1995
1995

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(9 citation statements)
references
References 9 publications
1
7
0
1
Order By: Relevance
“…Only 2 conceptions occurred with positive tests (N=26) against 9 in the negative group (N=20). These results show a significant difference (P< 0.01) and confirm the observation of Sullivan and Howe (1977). In 3 patients a positive pre-operative test reverted to negative after vasectomy reversal.…”
Section: Circulating Sperm Antibodiessupporting
confidence: 84%
“…Only 2 conceptions occurred with positive tests (N=26) against 9 in the negative group (N=20). These results show a significant difference (P< 0.01) and confirm the observation of Sullivan and Howe (1977). In 3 patients a positive pre-operative test reverted to negative after vasectomy reversal.…”
Section: Circulating Sperm Antibodiessupporting
confidence: 84%
“…The hypothesis that some cases of infertility have an immunological basis is plausible because vasectomy results in a high incidence of circulating autoantibody directed against sperm (1), and infertility after vasovasostomy is correlated with sperm agglutinins in serum (3) and semen (4). Infertility in vasovasostomized rhesus monkeys is also correlated with a high titer of circulating antibody to sperm (5).…”
Section: Tomy In Menmentioning
confidence: 99%
“…Antisperm antibodies develop in the serum of 60-80% of men following vasectomy [34, 351 but their effects on fertility following vasectomy reversal are poorly understood. Sullivan and Howe [80] found antibodies in the sera of 48% of men whose female partners were pregnant and 94% of those whose female partners were not pregnant, suggesting some relationship between these factors. The present authors found antibodies in the sera of 79% of 130 men presenting for vasectomy reversal: antibodies were found in seminal plasma in 9.5% of men before, rising to 29.5% after vaso-vasostomy [81].…”
Section: Vasectomy Reversalmentioning
confidence: 99%